Experimental and Numerical Investigation of the Effect of Turbulator on Heat Transfer in a Concentric-type Heat Exchanger - Budak, N.; Yucel, H. L.; Argunhan, Z. (Taylor & Francis Inc, 2016)
This article experimentally and numerically analyzes the effect of turbulators with different geometries (Type I, Type II, Type III, and Type IV) located at the inlet of the inner pipe in a concentric-type heat exchanger. Experiments were performed at parallel-flow conditions in the same and opposite directions to investigate the impact of manufactured turbulators on heat transfer and pressure drop. In the numerical study, ANSYS 12.0 Fluent code program was used, and basic protection equations were solved in the steady-state, three-dimensional, and turbulence-flow conditions. Results were obtained from numerical analysis conducted at different flow values of air (7, 8, 9, 10, 11, and 12m(3)/h). The distribution of temperature, velocity, and pressure was demonstrated as a result of numerical analyses. Experimental and numerical results were compared, and it was observed that they were in conformity with each other. When the data obtained from the analyses were examined, the highest heat transfer, pressure drop, and friction factor increase were detected to be in the Type IV turbulator.
Keywords: turbulator; numerical analysis; heat transfer enhancement; concentric heat exchanger